A first approach to the study of epizoic diatoms on marine benthic macroinvertebrates in Atlantic Patagonian waters (San Jorge Gulf) with SEM description of the most abundant taxa: Cocconeis patagonica sp. nov., Pseudogomphonema kamtschaticum and Tabularia investiens - Cefarelli, Adrián Oscar (2024)
Numerous organisms play a host role for a variety of marine and freshwater diatoms and many have yet to be studied in detail. In particular, along the Argentine coast, there have been very few studies on epizoic diatoms. Through the analysis of ascidians, decapods, echinoderms and gastropods sampled from Atlantic Patagonian waters (San Jorge Gulf), this is the first study in the region on epizoic diatoms found on benthic macroinvertebrates. Thirty–one potential host samples, including 14 macroinvertebrates taxa, were examined from different stations. The epizoic diatom taxa found at the highest relative abundance, namely Cocconeis patagonica sp. nov., Pseudogomphonema kamtschaticum and Tabularia investiens, were analyzed using light and electron microscopy, and hence they are described in detail and compared with other species. Cocconeis patagonica sp. nov. belongs to the C. scutellum complex, but its particular raphe–valve (RV) valvocopula ultrastructure and striation defines it as new. Diagnostic characters are discussed for T. investiens. Pseudogomphonema kamtschaticum is reported for the first time in the Atlantic Patagonian waters.